To land or not to land: How do stakeholders perceive the zero discard policy in European small-scale fisheries?. (September 2016) - Villasante, Sebastian; Pita, Cristina; Pierce, Graham J.; Guimeráns, César Pazos; Rodrigues, João Garcia; Antelo, Manel; Rocha, José María Da; Cutrín, Javier García; Hastie, Lee; Sumaila, Ussif Rashid; Coll, Marta
Abstract: The landing obligation recently adopted by the European Union's (EU) Common Fisheries Policy aims to eradicate discards in EU fisheries. The objective of this paper is to investigate the potential social and economic impacts of the discard ban in European small-scale fisheries (SSF) and the critical factors for its successful implementation. An exhaustive systematic literature review and a stakeholder consultation were carried out in order to (i) collect detailed information about current knowledge on discards in EU SSF and gauge stakeholder perceptions about potential impacts of the discard ban in European SSF, (ii) examine the capacity of the SSF industry to implement the discard ban, and (iii) explore the limits and feasibility of implementing such a measure. The results of this study show that little attention has been given by the scientific community to discards in EU SSF. Indeed, the systematic literature review shows that this problem is relatively unexplored in the EU. In addition, the effectiveness of a discard ban in industrial fisheries is still unclear, mainly because discard data are not systematically collected by fisheries authorities. Stakeholders mostly perceive that the new landing obligation was developed with industrial fisheries in mind and that compliance with the landing obligation in EU SSF will be difficult to achieve without high economic costs, such as those related to the handling and storage of unwanted fish on board. Highlights: The landing obligation recently adopted by the CFP is key to eradicate discards in EU fisheries. However, little attention has been given by the scientific community to discards in EU SSF. The discard problem in SSF is relatively unexplored in the EU. Heterogeneous characteristics of SSF raise concerns over its successful implementation. The landing obligation would be difficult to achieve without high economic costs.